The Effect Of Compound Exercises Using Aiding Means On Learning Side Scoring In Futsal For Players Aged 14 – 16 Years Old - Sabah, Noor; Hamid, Muaheb (Journal of Physical Education, 2021)
The researchers aim at designing compound exercises using aiding means for dribbling and scoring in futsal players aged 14 – 16 years old. They used the experimental method. The subjects were (20) young futsal players aged 14 – 16 years old. The data was collected using SPSS to conclude that aiding means have a positive effect on learning side scoring in futsal. Finally the researchers recommended stressing the use of compound skills in learning side scoring in futsal.